Diagnosis of Urinothorax: A rare Complication of Percutaneous nephrolithotomy and literature review - Chiara Cocelli; Shuyue Ren (Human Pathology Reports, 2024)
Urinothorax represents a very rare form of pleural effusion with significant clinical and laboratory variability making diagnosis difficult. We encountered a 63-year-old male who presented to the hospital for an elective right percutaneous nephrolithotomy for a staghorn calculus. Following this procedure, a novel right sided large pleural effusion was noted. Pleural studies were consistent with a pneumothorax and a likely urinothorax. Cloudy, amber, transudative pleural fluid was submitted for cytologic analysis. Cell morphology and immunohistochemical studies confirmed the clinical impression of urinothorax. This study shows that cytologic analysis with ancillary immunohistochemical stains is a convenient method for urinothorax diagnosis. Etiological identification of the pleural effusion is critical for patient management.